Transformation of economic education: from theory to sustainable development practice - Zakharova, K.F.; Захарова, Ксенія Федорівна (Львівський науковий форум, 2024)
The Sustainable Development Goals (SDGs) serve as a global compass, guiding humanity towards a more equitable and sustainable future. Economists, with their knowledge and skills, play a key role in achieving these goals. They shape economic policies, develop innovative solutions, and contribute to the transformation of economic systems. However, to effectively meet the challenges of today, higher education for economists still requires modernization, as the new realities of global initiatives are shaping new requirements for the training of specialists.
Keywords: Sustainable Development Goals (SDGs); economic education